2013
DOI: 10.3109/15368378.2013.800102
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila oogenesis as a bio-marker responding to EMF sources

Abstract: The model biological organisms Drosophila melanogaster and Drosophila virilis have been utilized to assess effects on apoptotic cell death of follicles during oogenesis and reproductive capacity (fecundity) decline. A total of 280 different experiments were performed using newly emerged flies exposed for short time daily for 3-7 d to various EMF sources including: GSM 900/1800 MHz mobile phone, 1880-1900 MHz DECT wireless base, DECT wireless handset, mobile phone-DECT handset combination, 2.44 GHz wireless net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 58 publications
1
16
0
3
Order By: Relevance
“…Next, 4 h postexposure, a notable increase in sporadic apoptotic cell death was detected during early (germarium 2b) and middle (stages 7-9) oogenesis. These findings not only reinforce our previous conclusions regarding the sensitivity of Drosophila ovarian tissue to RF radiation, 27 but are also consistent with earlier studies which have reported ROS-level upregulation and apoptosis activation in the germ-line cells of male rats, after their in vivo exposure to an RF field of 900 MHz. 35,36 Following a molecular-system and time-dependent specific rationale, we, next, investigated the transcriptional responses of ovarian cell sub-populations to RF radiation 2 h after the end of exposure, by a genomewide gene-expression profiling analysis and suitable correlations of the obtained data with available databases.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Next, 4 h postexposure, a notable increase in sporadic apoptotic cell death was detected during early (germarium 2b) and middle (stages 7-9) oogenesis. These findings not only reinforce our previous conclusions regarding the sensitivity of Drosophila ovarian tissue to RF radiation, 27 but are also consistent with earlier studies which have reported ROS-level upregulation and apoptosis activation in the germ-line cells of male rats, after their in vivo exposure to an RF field of 900 MHz. 35,36 Following a molecular-system and time-dependent specific rationale, we, next, investigated the transcriptional responses of ovarian cell sub-populations to RF radiation 2 h after the end of exposure, by a genomewide gene-expression profiling analysis and suitable correlations of the obtained data with available databases.…”
Section: Discussionsupporting
confidence: 93%
“…Among others, it may be this mobile-phone radiation-directed malfunction of yolk-protein metabolism that likely results in the observed reduction of Drosophila offspring-production efficiency, upon exposure to the particular stress, as it has been previously reported by our group. 27 Similarly, perturbation of embryonic Ratio is referred to the number of genes from our DEG list [comparison of their transcriptional activities between SE (sham exposed) and EXP (truly exposed) fly groups] divided by the total number of genes involved in each specific pathway that has been notably affected by flies' exposure to mobile-phone radiation. Threshold is determined at P value 0.05 [-log (0.05) D 1.30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased apoptotic cell death in D. melanogaster has also been found as a result of continuous or intermittent exposure to radiation from GSM mobile phones (Chavdoula et al, 2010;Margaritis et al, 2013) and also as a result of exposure to any known EMF source, including Wi-Fi (Wireless Fidelity) router, wireless DECT (Digital Enhanced Cordless Telecommunications) phone, blue-tooth, baby monitor, MW-oven (microwave), RF (radio frequency) generator (Margaritis et al, 2013). Bessho et al (1995) first described how high magnetic fields can affect growth and fertility in Caenorhabditis elegans.…”
Section: Introductionmentioning
confidence: 99%